Mayans & Aztecs, ancient lands of the Americas [videorecording (DVD)] - Carruthers, Bob; Whelan, Robert; Clegg, Richard; Lowe, Lara (Lost treasures of the ancient world., 2006)
Explores two great ancient Mexican civilizations, the war-like Aztecs and the peaceful Mayans, both of which have left a legacy in legend and architecture.